0556 Effectiveness of a Nasopharyngeal Airway Stent for Treatment of Obstructive Sleep Apnea. (27th April 2018) - Kushida, C; Ding, F; Endo, T; Satoh, M
Abstract: Introduction: Nasopharyngeal airway stents have been used in the treatment of obstructive sleep apnea (OSA), but have not been extensively evaluated in a systematic manner. Methods: The nasopharyngeal airway stent (NAS) under study is a single-use, flexible silicone-based tube that is inserted into one nostril and positioned so that it extends 1 cm below the free edge of the soft palate. Sixty-seven participants and 21 healthy controls at two sites had a pretreatment sleep study, wore the NAS at home, and returned for a follow-up sleep study while wearing the stent. Results: The combined results from the participants at both sites showed that the mean NAS pretreatment and posttreatment AHIs were 25.8 ± 20.1 and 19.5 ± 18.3 (P = 0.0001), respectively. The combined results were segregated by pretreatment OSA severity; participants with mean moderate and severe OSA severity showed significant posttreatment improvement compared to their pretreatment values, while those with mild OSA severity did not show a similar improvement. For the 21 individuals without OSA, the mean pretreatment and posttreatment AHIs were not significantly different. Conclusion: NAS represents an OSA treatment which is effective, particularly for those with moderate-to-severe OSA, easy to use, disposable/single use, well tolerated, and convenient for travel. Support (If Any): This study was sponsored by Seven Dreamers Laboratories, Inc.